2015
DOI: 10.1038/hdy.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Interglacial refugia preserved high genetic diversity of the Chinese mole shrew in the mountains of southwest China

Abstract: The mountains of southwest China (MSC) harbor extremely high species diversity; however, the mechanism behind this diversity is unknown. We investigated to what degree the topography and climate change shaped the genetic diversity and diversification in these mountains, and we also sought to identify the locations of microrefugia areas in these mountains. For these purposes, we sampled extensively to estimate the intraspecific phylogenetic pattern of the Chinese mole shrew (Anourosorex squamipes) in southwest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…The ENM analyses also indicate the existence of more stable climatic conditions in the southern portion of the current distribution of S. fusicaudus (i.e., south of 29° N, Figure f; see Zhang, Boufford, Ree, & Sun, ). Although we acknowledge that our ecological niche model was not projected onto climatic scenarios older than ~120,000–140,000 years BP, much shorter than the evolutionary timeframe estimated for the origin of S. fusicaudus (projections onto older climatic scenarios require special considerations, assumptions and perhaps a more robust dataset of occurrences), the patterns shown by our ENM analyses coincide with the unevenly distributed genetic diversity in this taxon (Figure ), indicating that the higher diversity in the southern region of the sky islands is associated with a larger number of interglacial refugia (He et al, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ENM analyses also indicate the existence of more stable climatic conditions in the southern portion of the current distribution of S. fusicaudus (i.e., south of 29° N, Figure f; see Zhang, Boufford, Ree, & Sun, ). Although we acknowledge that our ecological niche model was not projected onto climatic scenarios older than ~120,000–140,000 years BP, much shorter than the evolutionary timeframe estimated for the origin of S. fusicaudus (projections onto older climatic scenarios require special considerations, assumptions and perhaps a more robust dataset of occurrences), the patterns shown by our ENM analyses coincide with the unevenly distributed genetic diversity in this taxon (Figure ), indicating that the higher diversity in the southern region of the sky islands is associated with a larger number of interglacial refugia (He et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…To calculate the Bayes factor, the marginal likelihood of each analysis was estimated with 1,000,000 steps. The two fossil-based calibrations were used as "checkpoints", constraining the times of diversification (He, Hu, Chen, Li, & Jiang, 2016;Mercer & Roth, 2003). We considered Bayes Factor ≥10 as strong evidence against the alternative hypothesis (Kass & Raftery, 1995).…”
Section: Phylogenetic Relationships and Divergence Timementioning
confidence: 99%
“…These ecophysically varied zones result in a complex of sky islands (He & Jiang, 2014;McCormack, Huang, Knowles, Gillespie, & Clague, 2009). Many studies have revealed coarse genetic structure and substantial population changes among ecological generalists and/or widespread species in the MSC (He, Hu, Chen, Li, & Jiang, 2016;Liu, Chen, et al, 2012;Qu et al, 2015;Wang et al, 2013), while some ecological specialists and/or sedentary species appear to have finer genetic structure and stable population sizes over time (Chen et al, 2015;Lu et al, 2012;Yan et al, 2013;Zhang et al, 2010). The contrasting patterns may be due to intrinsic traits among species, such as physiology and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested that the LIG (Last Interglacial Maximum) was an 8 unfavorable period for mole shrews (Anourosorex squamipes) because of increased seasonality in temperature extremes. During this period, mole shrews survived in 10 isolated interglacial refugia mainly located in the southern subregion and then rapidly expanded during the LGM (He et al 2016). The amount and distribution of suitable 12 habitat for snub-nosed monkeys also is likely to have been affected by these climatic events.…”
Section: Demographic History and Correlation With Climate Changementioning
confidence: 99%